2016
DOI: 10.1080/14397595.2016.1226469
|View full text |Cite
|
Sign up to set email alerts
|

Ganglionic acetylcholine receptor autoantibodies in patients with autoimmune diseases including primary biliary cirrhosis

Abstract: The results demonstrated a significant prevalence of anti-gAChR antibodies in patients with AID, which is independent of the production of other autoantibodies in patients with autoimmune diseases. These anti-gAChR antibodies could mediate the autonomic dysfunction involved in the autoimmune mechanisms of AID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…As described above, sweating of SSc patients has been believed to be impaired because collagen accumulation causes atrophy of the sweat glands. Our unexpected results suggest the possibility that sweating is regulated by the autonomic nervous system (13,14), and it may be stimulated for unknown reasons in SSc patients. Alternatively, because skin sclerosis of the finger pads is usually mild, there may be compensatory hyperhidrosis.…”
Section: Discussionmentioning
confidence: 79%
“…As described above, sweating of SSc patients has been believed to be impaired because collagen accumulation causes atrophy of the sweat glands. Our unexpected results suggest the possibility that sweating is regulated by the autonomic nervous system (13,14), and it may be stimulated for unknown reasons in SSc patients. Alternatively, because skin sclerosis of the finger pads is usually mild, there may be compensatory hyperhidrosis.…”
Section: Discussionmentioning
confidence: 79%
“…They include systemic lupus erythematosus (SLE), systemic sclerosis (SSc),, Still's disease, rheumatoid arthritis (RA), Hashimoto's disease and Graves’ disease, which often manifest skin symptoms. Recent studies revealed that gAChR antibodies were detected in sera from patients with SLE (12.5%), SSc (13.2%) and RA (18.6%), implicating the pathogenic significance of anti‐gAChR antibodies in these autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We determined the associations between autonomic dysfunction and anti-gAChR antibodies in SSc, SLE, and RA using the LIPS assay. The LIPS assay detected anti-gAChRα3 and β4 antibodies in the sera of patients with SSc (13.2%, 5/38), SLE (12.5%, 4/32), and RA (18.6%, 8/43) [17].…”
Section: Case Series and Prevalence Of Anti-gachr Antibodies In Systementioning
confidence: 99%
“…We performed the LIPS analysis with the α3 or β4 subunit fused to Gaussia Luciferase 8990 to measure the respective antibodies in human sera [9,14]. Recently, we determined the prevalence of anti-gAChR antibodies in autoimmune rheumatic diseases (ARD) including SS, SSc, RA, and SLE with this method [15][16][17]. In the present review, we aimed to critically examine the current literature on autonomic neuropathy and autonomic function tests and to propose that anti-gAChR antibodies provide a new perspective on the mechanism underlying autonomic dysfunction in ARD.…”
Section: Introductionmentioning
confidence: 99%